2021
DOI: 10.3390/jcm10194356
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Mechanical and Biological Prostheses in Patients with Left-Side Infective Endocarditis: A Systematic Review and Meta-Analysis

Abstract: Background. Long-term outcomes of patients with infective endocarditis (IE) who received either a mechanical (MP) or biological prosthesis (BP) are conflicting. A meta-analysis of observational studies comparing the long-term outcomes of left-side IE with the use of MP versus BP was performed. Methods. Electronic databases from January 2000 to June 2021 were screened. Studies reporting long-term mortality were analyzed. The primary endpoint was long-term overall mortality. Secondary endpoints were in-hospital/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Our study showed no significant difference in early mortality among patients treated with mechanical vs. biological prostheses. The overall early mortality rate was 6.2% after AVR for IE, consistent with mortality rates reported in the literature [1,18,19]. In our series, patients receiving a mechanical prosthesis had a significantly lower occurrence of atrial fibrillation and acute kidney injury.…”
Section: Perioperative Outcomes Long-term Survival and Recurrence Of ...supporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed no significant difference in early mortality among patients treated with mechanical vs. biological prostheses. The overall early mortality rate was 6.2% after AVR for IE, consistent with mortality rates reported in the literature [1,18,19]. In our series, patients receiving a mechanical prosthesis had a significantly lower occurrence of atrial fibrillation and acute kidney injury.…”
Section: Perioperative Outcomes Long-term Survival and Recurrence Of ...supporting
confidence: 90%
“…Contradictory results have been reported for long-term survival in patients undergoing AVR with mechanical prostheses versus bioprostheses for IE [ 4 , 5 , 6 , 19 , 20 , 21 ]. A propensity-weighted observational study on 395 patients with left-sided endocarditis in patients over 18 years of age showed lower mortality at 10 years, 51.4 ± 6.3% versus 73.7 ± 12.0%, for the mechanical valve group vs. biological valve group.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory results have been reported for long-term survival in patients undergoing AVR with mechanical prostheses versus bioprostheses for IE [4][5][6][19][20][21]. A propensityweighted observational study on 395 patients with left-sided endocarditis in patients over 18 years of age showed lower mortality at 10 years, 51.4 ± 6.3% versus 73.7 ± 12.0%, for the mechanical valve group vs. biological valve group.…”
Section: Perioperative Outcomes Long-term Survival and Recurrence Of ...mentioning
confidence: 99%